Pengaruh Konten Sepakbola Liga Inggris di Aplikasi Vidio terhadap Minat Menonton Grup Manchester United Fans Indonesia di Telegram - Kelvin Roberto Maksindo Manurung; Oky Oxcygentri; Ema (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Football has a global appeal, including in Indonesia, as reflected by the high level of public interest in the sport. The advancement of technology allows fans to watch matches through services such as Vidio. This study focuses on the use of football services and fan communities, specifically the "Manchester United Fans Indonesia" group on Telegram. The aim of this research is to examine the extent to which football content from the English Premier League on the Vidio app influences the viewing interest of the Manchester United Fans Indonesia group on Telegram. This study applies the Uses and Effects theory and utilizes a descriptive quantitative method, with probability sampling techniques and random sampling. The sample consists of 93 members from the Manchester United Fans Indonesia group on Telegram. The results indicate that the football content of the English Premier League significantly influences the viewing interest of the Manchester United Fans Indonesia group on Telegram. This is evident from the correlation coefficient (R^2) of 0.705 and the coefficient of determination (R²) of 0.498. This indicates that the variable X (English Premier League content on the Vidio app) influences variable Y (viewing interest of the Manchester United Fans Indonesia group on Telegram) by 49.8%, while the remaining variance is influenced by other factors not included in this study.